2018
DOI: 10.1016/j.clinbiochem.2017.10.012
|View full text |Cite
|
Sign up to set email alerts
|

Clustered interventions to reduce inappropriate duplicate laboratory tests in an Irish tertiary hospital

Abstract: The interventions resulted in sustained reduction in rates of inappropriate testing by May 2014. Extrapolated cost reductions exceed two million Euro annually. The most effective intervention involved staff education.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…in transfers between emergency departments, duplication rates of 32 to 88% have been found. (7)(8)(9)(10)(11) Repetition rates for patients being transferred from general practice to the hospital have been studied less extensively. One study, investigating repetition rates for patients who were admitted to the medical department of a hospital found that 63% of tests ordered by the general practitioners in the previous year were repeated on admission.…”
Section: Introductionmentioning
confidence: 99%
“…in transfers between emergency departments, duplication rates of 32 to 88% have been found. (7)(8)(9)(10)(11) Repetition rates for patients being transferred from general practice to the hospital have been studied less extensively. One study, investigating repetition rates for patients who were admitted to the medical department of a hospital found that 63% of tests ordered by the general practitioners in the previous year were repeated on admission.…”
Section: Introductionmentioning
confidence: 99%